Meat Quality Of Raw Materials Nuggets Laying Chicken Rejects - Endah Subekti (MEDIAGRO, 2010)
Nuggets is one of the processed meat product in a restructuring. Meatin the manufacture of nuggets can be obtained from various types oflivestock, livestock type and age of cattle, for example from beef, buffalomeat, rabbit meat, mutton and meat of laying hens rejected. Quality ofnuggets as the restructuring of meat products is determined by the ability ofeach binding between the particles of meat and other ingredients are added,so the starch as binder. Gelatinization process that will determine the qualitynuggets related to the concentration of starch is added and the temperaturesteaming. Gelatinization temperature during steaming should be appropriateto improve the quality of chicken nuggets which have a layer rejects toughnature. Therefore it needs to do research about the quality of chickennuggets laying rejected by the addition of starch and different longsteaming. From the results of this research can be concluded that the type ofchicken meat does not give effect to the elasticity, organoleptic test scoretexture, appearance and porosity nuggets of chicken, use chicken nuggetslaying rejects giving a better quality than broiler meat. Nuggets by using themeat of laying hens rejects and tapioca 30% and 50 minutes long steamingbest treatment.Key Words : Quality, Nuggets, Laying chicken rejects